IDENTIFICATION AND MAPPING OF CRITICAL LAND LEVELS IN THE KRUENG LANGSA WATERSHED USING GEOGRAPHIC INFORMATION SYSTEM: IDENTIFIKASI DAN PEMETAAN TINGKAT LAHAN KRITIS DI DAERAH ALIRAN SUNGAI KRUENG LANGSA MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Iswahyudi; Elita Romei Tampubolon; Rosmiati (ROCE : Jurnal Pertanian Terapan, 2026)
Langsa City has a river that runs through the city, namely the Krueng Langsa. Critical land will disrupt the land’s ability to regulate water management, flood control, and sedimentation in downstream areas. The method used by GIS is a weighted scoring analysis: the weighted overlay method, the scoring method, and the weighted overlay.   The weighted overlay is a spatial analysis technique that overlays multiple maps related to the factors affecting the vulnerability assessment. The analytical tool used is the geographic information system (GIS). The search parameters were the sloping map, the erosion risk map, the land use map, and the land management map. The results for land importance in the Langsa River showed that it falls into three categories: not important, potentially important, and slightly important. The most predominant land type was unimportant, covering 13,269.23 ha (65.31%), followed by potentially important land, covering 7,030.22 ha (34.60%). These two land importance criteria were found in Langsa Baro District, Langsa West District, Langsa Lama District, Langsa East District, and Langsa City District. “The Slightly Critical class is the smallest class which is only found in Langsa Lama District, specifically in Pondok Factory Village and Petow Village, which are geographically located between 04◦ 42’ 23.99” N – 04◦ 44’ 68.91” N North Latitude and 97◦ 91’ 86.81” E – 97◦ 90’41, 99” N with an area of 15.12 ha (0.07%).